Program Evaluation Novel Study in Improving Junior High School Students English Language Skills: The CSE-UCLA Model Approach - Purwaningsih, Sri; Madani, Faisal; Priyanto, Sugeng (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This article aims to evaluate the Novel Study Program implemented in SMP An Nisaa as a strategy to improve students' English language skills. The program involves novel reading activities, learning by native speakers, and drama performances. The evaluation was conducted using a descriptive qualitative approach using the CSE- UCLA model, which consists of five evaluation functions: system assessment, program planning, program implementation, program improvement, and program certification. Data were collected through interviews, observations, questionnaires, and documentation studies. The evaluation results showed that the program had a positive impact on students' interest and confidence in using English. The evaluation also revealed several technical aspects that need to be improved in its implementation. This article recommends strengthening local teacher support and integrating mentor training for students.